Broad view of cryptographic hash functions - Alahmad, Mohammad; Alshaikhli, Imad Fakhri Taha (IJCSI Press, 2013)
Cryptographic hash function is a function that takes an arbitrary length as an input and produces a fixed size of an output. The viability of using cryptographic hash function is to verify data integrity and sender identity or source of information. This paper provides a detailed overview of cryptographic hash functions. It includes the properties, classification, constructions, attacks, applications and an overview of a selected dedicated cryptographic hash functions.